Agrarian Conflict Handling Policy in the Tourism Village Development Program in the Lake Toba Area - Rosiani, Lutfia Dwi; Amrullah, M. Nur Kamila (Marcapada: Jurnal Kebijakan Pertanahan, 2024)
Lack of public knowledge about land ownership and the inability of the public to control emotions in solving problems can trigger conflicts, both conflicts of interest and agrarian conflicts. Furthermore, local government policies that are not firm enough in dealing with people who do not fully understand land ownership and assets that cannot be controlled by individuals are also factors in agrarian conflicts. Agrarian conflicts in each region are different, but it is possible that the causal factors and chronology are the same as in other regions. This paper aims to discuss local government policies in handling agrarian conflict cases. Interviews were the method used. We use interview techniques to explore the chronology of conflict cases and their resolution. The study employs qualitative data analysis techniques. The study's results demonstrate that related parties engage in deliberation to implement the policy for handling agrarian conflicts. The land office's role in conflict resolution is to provide land administration services. Once the Ombudsman of the Republic of Indonesia receives a case report, they must proceed through several stages before issuing a decision letter. Only the Regency Government and the Land Office must cooperate by adhering to the stages and participating in the Ombudsman's examination.